Effect of maintenance therapy for childhood with acute lymphoblastic leukaemia by combination of methotrexate and 6-mercaptopurine on the liver. - Abid T. Firas; Al-Fakhri F. Ilham (College of Pharmacy / Mustansiriyah University, 2005)
Seven of 30 children with acute lymphoblastic leukaemia (ALL) receiving maintenance therapy (MT) consisting of daily oral 6-mercaptopurine (6MP) and weekly methotrexate (MTX) developed both hepatocellular destruction and intrahepatic cholestasis (with abnormally elevated levels of serum aminotransferases enzymes GOT, GPT that mainly indicate liver cell destruction, and alkaline phosphatase, gammaglutamyl transferase enzymes, as well as total serum bilirubin that mainly indicate biliary tract disorder). In the remaining 23 patients, the serum levels of alkaline phosphatase (ALP), gammaglutamyl transferase (GGT) enzymes, and total serum bilirubin (TSB) . were within the normal reference ranges for these parameters of the liver function tests while 13 patients. have abnormally elevated serum glutamic oxaloacetate transaminase (GOT) and glutamic pyruvate transamiase (GPT). The long-term use of MTX (20 mg/m2/week) and 6MP (75 mg/m2/day) during the MT for childhood ALL may lead to the development of hepatocellular destruction mainly induced by MTX, and intrahepatic mainly induced by 6MP.